Exploring the Role of Radiation Physics in the Design and Safety of Medical Devices - Karim, Zaid Fadhel; Uljabar, Mawzar Abd Ulsatar Abd; Aliwi , Taiba Mushtaq; Sami, Mays Adel; Mukhlef, Mohammed Thamer (American Journal of Botany and Bioengineering, 2025)
Radiation physics investigates the production, propagation and interaction of ionising and non-ionising radiation with matter, especially in biological systems. Knowledge of radiation physics is essential for the development, assessment and application of radiation sources. Medical devices typically use radiation sources or exposed medicines. Most often, devices using radiation emit it. This article provides a brief overview of the main types of radioactive sources; x-ray and gamma-ray tubes; radioisotopes and brachytherapy sources; linear accelerators or betatrons; plasma generators and open convolution accelerators; portable, pulsed or stationary devices, and the possible safety hazards created by their use. Radiation is the emission or transmission of energy in the form of waves. Waves are periodic disturbances of physical quantity. Various types of waves exist, classified according to their amplitude (mechanical or nonlinear waves), propagation mode (longitudinal, transverse or surface waves), propagation medium (elastic or electromagnetic waves), frequency/diameter (seismic waves) or other phenomena (solitons, gravity waves). Radiation can be treated as an electromagnetic wave – a periodic disturbance of electric and magnetic fields propagating space. Constructive and non-destructive interference creates various radiation-based instruments and devices: telescopes, microscopes, cameras, delimiters, cloaking devices, projectors, screens and memories, among others . Radiation was discovered by Henri Becquerel in 1896 and shortly afterward studied and named by Pierre and Marie Curie. It was soon discovered how to isolate radioactive isotopes from ore rocks. Hermann Wilhelm Göring built the first atomic power plants, and Leo Szilard designed the A-bomb split- and fusion-based more powerful H-bombs. There are three types of radioactive decay: particle radiation, where an atom loses electrons (beta decay), protons or neutrons (alpha decay) or spits a nucleus of heavier isotope (spontaneous radioactive decay); wave radiation, where highly excited electrons of heavy ions spout inner-core electrons and cephalone cavity x-ray imaging creation of monochromatic x-ray beam; and transportable particle radiation, where nuclear reactors or isotopes are used to generate energy (alpha particle emission, 238U, 9-20 MeV, radon gas pollution hazards) or gamma-ray imaging to find and neutralise these isotopes. Dangerous isotopes are those with low threshold energy.